Assessing benefits and risks between the space economies and the sustainable development goals - Cernev, Tom; Bland, Jessica; Zilgalvis, Gustavs; Kaleagasi, Bartu; de Zwart, Melissa; Tzachor, Asaf; Richards, Catherine E.; Chesley, Bruce; McClintock, Bruce; Agachi, Anca (Frontiers in Space Technologies, 2024)
As humanity's presence in space continues to advance, it is important to consider the positive and negative effects of space activities on sustainable development. This paper presents the findings from an expert elicitation process to assess the benefits and risks of the Earth-for-space, space-for-Earth, and space-for-space economies for the United Nations' Sustainable Development Goals (SDGs).Significant benefits and risks exist, with SDGs 6, 9, 12, 14, and 16 exhibiting numerous benefits, and SDGs 6, 8, 11, and 15 exhibiting various risks from activities across the space economies. Multisectoral, multi-disciplinary experts have identified benefits including space as a means to facilitate international agreement and cooperation, insights from space-based Earth observation, and advances in economic and technological development. Conversely, they identified risks of space advancement resulting in inequality, overexploitation of space resources, and the increase of global geopolitical tensions. These findings were used to suggest an SDG 18 for space, consisting of seven targets that address the concerns raised in the process.